Retrospective analysis of the production of the Revue d’anthropologie des connaissances - The Editorial Board (Revue d'anthropologie des connaissances)
Based on the corpus of all articles published during the ten-year existence of the Revue d’Anthropologie des Connaissances, this article offers a retrospective analysis of the status of authors, of the categories of published items, of contents of abstracts and keywords, and of references enlisted in the contributions. This analysis makes it possible to understand what the editorial project has generated during the 10 years of publication of the journal with regard to its editorial project and its willingness to foster an open science. This retrospective analysis leads to a synthesis of the way in which the Revue d’Anthropologie des Connaissances contributes to the landscape of scientific publishing today.